2020
DOI: 10.1142/s1793524520500758
|View full text |Cite
|
Sign up to set email alerts
|

Pythagorean m-polar fuzzy topology with TOPSIS approach in exploring most effectual method for curing from COVID-19

Abstract: The corona virus disease 2019 (COVID-19) has emerged as a fatal virus. This deadly virus has taken the whole world into clutches and many people have embraced death due to this invincible bug. The death toll is rising with every tick of time. The aspiration behind this article is to discover the preventive measure that should be taken to cope with this intangible enemy. We study the prime notions of novel sort of topology accredited Pythagorean [Formula: see text]-polar fuzzy topology along with its prime attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The authors proposed a rescue framework for the transfusion of the best convalescent plasma (CP) to the most critical patients while considering ML and MADM, which can greatly assist the health sector when such decisions are to be made. Another study 67 discussed exploring the most efficient method for surviving COVID‐19 in addition to medical treatments. For this purpose, the authors introduced a novel concept of the MADM technique and explored the most effective alternative cure for COVID‐19, which is undoubtedly based on the theory and work they applied.…”
Section: Literature Review Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The authors proposed a rescue framework for the transfusion of the best convalescent plasma (CP) to the most critical patients while considering ML and MADM, which can greatly assist the health sector when such decisions are to be made. Another study 67 discussed exploring the most efficient method for surviving COVID‐19 in addition to medical treatments. For this purpose, the authors introduced a novel concept of the MADM technique and explored the most effective alternative cure for COVID‐19, which is undoubtedly based on the theory and work they applied.…”
Section: Literature Review Analysismentioning
confidence: 99%
“…The devastating effect of the COVID‐19 pandemic has created an unprecedented situation that needs a professional decision support system that can effectively handle the related issues mentioned in Table 1 . The result of this review revealed 13 extensions of existing methods, namely, LBWA–MACBETH–RAFSI, 49 PmF‐TOPSIS, 67 WASPAS, 95 AHP‐Entropy‐TOPSIS‐GRA, 78 distance measure for IFSs, 59 LHF‐BWM‐TODIM, 96 BBWM with improved matter‐element extension model (BBWM‐IMEEM), 90 cross‐entropy of UPLZs‐MULTIMOORA, 74 Entropy‐F‐VIKOR, 89 FAHP‐HFS‐TOPSIS, 80 HF‐divergence measure‐HF‐ARAS, 76 TrIT2F‐BWM‐VIKOR, 72 and IF‐MARCOS. 92 These methods mainly focus on handling the inaccuracies and uncertainties (vagueness issue) mentioned in Table 1 .…”
Section: Literature Review Analysismentioning
confidence: 99%
“…e determined alternative scheme should be located at the shortest geometric distance from the optimal scheme and the longest geometric distance from the worst scheme [30]. As a multicriteria decision analysis method, TOPSIS has been successfully applied to industrial technology [31,32], computer science [33][34][35], medical problems [36], applied statistics [37][38][39][40], environmental protection [41,42], and other fields.…”
Section: Topsis Methodmentioning
confidence: 99%
“…Ashraf et al, 16 introduced the technique for emergency response using spherical intelligent fuzzy decision process to diagnose COVID‐19. Naeem et al, 17 proposed the Pythagorean m‐polar fuzzy topology based TOPSIS approach to explore the most effectual method for curing from COVID‐19.…”
Section: Introductionmentioning
confidence: 99%